RUPIAH CURRENCY INTRODUCTION PROGRAM FOR CHILDREN OF MIGRANT WORKERS IN MALAYSIA - Gymnastiar, Iman Ahmad; Roisah, Roisah; Azizah, Siti Nur; Shahla, Nazwa Khaira; Azhahra, Almahira Putri; Nelson, Feby; Simorangkir, Prita Laura Angelica; Nugroho, Septian Widyo; Maulidah, Syarofina Izna; Syifa, Nurul Mustika; Nugraha, Aditya Setya; K, Intan Duta Swara; Bachri, Sagita Nur; Pratama, Alga (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2024)
This program's goal is to enhance the understanding and skills of the children of Indonesian migrant workers in Malaysia in recognizing and understanding the Rupiah currency. Through an interactive and creative approach, this program combines information technology, mock money, and hands-on teaching to 32 children in Malaysia.. The results of this program include children's ability to demonstrate methods of distinguishing between natural and imitation currency, an understanding of how to care for money properly, the ability to compare the value of Ringgit and Rupiah currency, and the ability to recognize, sort and count the amount of Rupiah currency. This program provides practical knowledge of currency and engages children in activities supporting essential financial skills development. With the involvement of the Indonesian Young Spirit, this program is a form of positive contribution in equipping the children of migrant workers with relevant knowledge to face life in Malaysian society.